THE HIDDEN PROPAGANDA OF U.S HEROISM IN Iron Man 1 & IRON MAN 2 MOVIES - Mukhairisubarkah, Rezarivano; Kurniawan, Yusuf (Universitas Muhammadiyah Surakarta, 2023)
This research discusses how the U.S. launched its propaganda of American heroism through the film as the medium. This study is classified as qualitative research. The technical analysis of the data used in this research is the technical analysis of qualitative data from Miles and Huberman. The source of information or data for this research are Jon Favreau's Iron Iron Man 1 (2008) and Iron Man 2 (2010) films. The data are the captured scenes and dialogues from the film Iron Man 1 Iron Man 2. A scene can consist of several frames and dialogs that describe the storylines in a scene. The results of the data analysis obtained a list of scenes that contain propaganda techniques. Since the data was in the form of movie scenes, Pierce's semiotics and Villarejo's cinematic theory are used to examine the data. In conclusion, the movie shows several aspects that support the findings in the analysis of American heroism and its maintenance in the movie. The representation comes from how the United States in the movie uses its military power, the perspective of seeing other nations, and shows the U.S has more advanced technology than other countries.